(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The European Parliament’s 2022 Resolution on Global Threats to Abortion Rights promotes a wide-ranging and women-focused approach to sexual and reproductive health and rights, which continue to be in jeopardy globally, and have worsened following the US Supreme Court’s Dobbs ruling. The Resolution’s most striking aspect is a call for the right to abortion to be included in the European Union’s Charter of Fundamental Rights. The legal effects of such an inclusion would be limited, although potentially improving cross-border access to abortion. Union law remains a legally constrained space for pursuing abortion rights.